2002
DOI: 10.1002/bio.695
|View full text |Cite
|
Sign up to set email alerts
|

Rapid determination of rice seed vigour by spontaneous chemiluminescence and singlet oxygen generation during early imbibition

Abstract: Using a highly sensitive single photon counter, a spontaneous chemiluminescence (CL) study on rice (Oryza sativa L.) seeds stored in different years was carried out. We first observed that the degree of ageing in rice seeds was related to the intensity of spontaneous CL during early imbibition (0-30 min). Rice seeds stored for a shorter time had a stronger intensity of CL in early imbibition. The germination rate of rice seeds showed an obvious positive correlation with the intensity of spontaneous CL. Singlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…As a result, UWPE from seeds has been employed as a rapid means of evaluating seed quality and viability. For cereal seeds, for example, it is possible, after only a few minutes of imbibition, to distinguish those seeds which will produce stronger sprouts upon germination from those which will be weaker (Chen et al 2003). Then, during the subsequent growth period, the whole of each seedling emits light, the source of the luminescence being the radicle, the cotyledon, and the endosperm, the latter tissue, perhaps because of its greater mass and rapid catabolic metabolism, producing the greatest signal (Chao 1998).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, UWPE from seeds has been employed as a rapid means of evaluating seed quality and viability. For cereal seeds, for example, it is possible, after only a few minutes of imbibition, to distinguish those seeds which will produce stronger sprouts upon germination from those which will be weaker (Chen et al 2003). Then, during the subsequent growth period, the whole of each seedling emits light, the source of the luminescence being the radicle, the cotyledon, and the endosperm, the latter tissue, perhaps because of its greater mass and rapid catabolic metabolism, producing the greatest signal (Chao 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Q 10 = 2) (3) in the range 303-323°K are critical for the generation of excited electronic states which lead to the observed CL. Our previous results (6) showed that rice seeds with a longer storage time had a lower intensity of CL during early imbibition, and the germination rate of rice seeds showed a significant positive correlation with the intensity of spontaneous CL. Our previous report suggested that there was production of active oxygen (6).…”
Section: Discussionmentioning
confidence: 88%
“…Our previous results (6) showed that rice seeds with a longer storage time had a lower intensity of CL during early imbibition, and the germination rate of rice seeds showed a significant positive correlation with the intensity of spontaneous CL. Our previous report suggested that there was production of active oxygen (6). We believe that the production of active oxygen must be related to enzyme reactions.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It has been shown that the interaction between water and dry cereal grains, flour and bread products results in much stronger CL [3,4,5]. Our previous report [6] showed that rice seeds with longer storage time had lower intensity of spontaneous CL during early imbibition, the germination rate of rice seeds showed a significant positive correlation with the intensity of spontaneous CL, the experimental results demonstrated that UCL in rice seeds during early imbibition could be attributed mainly to singlet oxygen ( 1 O 2 ). Seed germination can be separated into three distinct phases [7].…”
Section: Introductionmentioning
confidence: 95%